Language, Thought, and Reality - Benjamin Lee Whorf (The MIT Press, 2012)
This little book has had an extraordinary career. 1 Initially admired, then reviled, then rehabilitated, then once again attacked, it has proved unsinkable. This is all the more surprising given the contents: a handful of rather dated papers on Amerindian linguistics, a couple on ancient Mesoamerican writing systems (also now dated), four papers for a general audience about language differences, and some unfinished manuscripts found among the papers of the author after his premature death. This is not the kind of material that one would have expected to inflame the passions or rouse phlegmatic scholars of linguistics and psychology from their detailed and meticulous pursuits. How surprising, then, that Pinker (1994 , 57) announces, â€œ But it is wrong, all wrong, â€ or that Deutscher (2010 , 21) calls Whorf â€œ that most notorious of con men. â€ (For the other side of the story, see Lucy 1992a; Lee 1996 , 2000 .) Why has this book caused such a row, a flaming controversy that continues over a half century later? One reason is that the ideas sketched in the book suggest that the structuring of particular languages is altogether too interesting to be left to the plodding philologists, and specifically that the implicit patterning in languages might have something to do with how we think, whatever the psychologists tell us. Simple exposure to this message has turned on generation after generation of students; suddenly the arbitrary rules and conventional clothing of languages seem to have a new significance. Over a beer, many eminent researchers in the language sciences will confess that they were first drawn into the study of language through the ideas associated with Benjamin Lee Whorf. In short, a seductive, revolutionary set of ideas is buried in these pages, and they are in a form that permits enough latitude of interpretation to rekindle the flames of controversy at any point.